Generalized equilibrium problem with mixed relaxed monotonicity - Rizvi, Haider Abbas; Kilicman, Adem; Ahmad, Rais (Hindawi Publishing Corporation, 2014)
We extend the concept of relaxed α -monotonicity to mixed relaxed α - β -monotonicity. The concept of mixed relaxed α - β -monotonicity is more general than many existing concepts of monotonicities. Finally, we apply this concept and well known KKM-theory to obtain the solution of generalized equilibrium problem.